A state-of-art approach to misbehaviour detection and revocation in VANET: survey. (2018) - Singh, Dinesh; ,; Yadav, Rama Shankar
With the increased popularity of internet application and smart cities, vehicular ad hoc networks (VANETs) have become one of the prominent research area and ample of researchers have addressed the many issues in the past decade. Among the many issues involves with effective VANET, misbehaviour detection and revocation is required to address with full attention. It is first and foremost step towards dealing with safety applications in VANETs. The vehicle misbehaviour is responsible for malfunctioning of many network activities (e.g., traffic jam, road accidents etc.). The misbehaviour detection problem becomes more severe for safety critical applications in VANETs. The misbehaved vehicle must be revoked from the network as early as possible to reduce injuries. Thus, inconjuction of misbehaviour detection, revocation problem also needs to be explored. This paper is addressed to provide state-of-art to misbehaviour detection and revocation for safety critical VANETs. Here we present a detailed survey on relevant research done in the area of misbehaviour detection and revocation with other related issues.